2019
DOI: 10.2166/nh.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

Regional rainfall response to the North Atlantic Oscillation (NAO) across Great Britain

Abstract: The North Atlantic Oscillation (NAO) has been long studied as the primary teleconnection affecting the British and European climate. However, previous studies have focused on extremes or have been spatially and temporally limited. In recent years, our ability to predict the NAO has improved. Also, new research is emerging, suggesting that the NAO is a key driver of hydrological extremes. These factors mean that there is a renewed value in enhancing our understanding of how the NAO influences general rainfall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 48 publications
11
45
0
Order By: Relevance
“…The study of drought frequency trend analysis (Section "Results -Trend Analysis, " Figure 7) and the timeline of historic droughts (Section "Historic Timeline of Droughts, " Figure 10 and Supplementary Figure 1) highlighted the existence of an apparent alternation between severe droughts in the NW and the SE for long accumulation periods (12 and 24 months), with clusters of droughts in the SE occurring 1920-1940and 1975-2000and droughts in the NW occurring 1860-1900and 1940-1975. This pattern coincides with decadal fluctuations in the winter North Atlantic Oscillation (NAO) index (Hurrell, 1995;Visbeck et al, 2001), proven to be correlated to precipitation levels in the NW (Wilby et al, 1997;West et al, 2019). Negative winter NAO indices are known to be linked to lower FIGURE 13 | Percentage of months in the most severe droughts affecting the three regions.…”
Section: Historic Droughtsmentioning
confidence: 53%
“…The study of drought frequency trend analysis (Section "Results -Trend Analysis, " Figure 7) and the timeline of historic droughts (Section "Historic Timeline of Droughts, " Figure 10 and Supplementary Figure 1) highlighted the existence of an apparent alternation between severe droughts in the NW and the SE for long accumulation periods (12 and 24 months), with clusters of droughts in the SE occurring 1920-1940and 1975-2000and droughts in the NW occurring 1860-1900and 1940-1975. This pattern coincides with decadal fluctuations in the winter North Atlantic Oscillation (NAO) index (Hurrell, 1995;Visbeck et al, 2001), proven to be correlated to precipitation levels in the NW (Wilby et al, 1997;West et al, 2019). Negative winter NAO indices are known to be linked to lower FIGURE 13 | Percentage of months in the most severe droughts affecting the three regions.…”
Section: Historic Droughtsmentioning
confidence: 53%
“…Our results show that Clusters 2, 3 and 5, which cover most of Europe, are transitional regions that exhibit stronger non-stationarity than those of relative stationarity (Clusters 1 and 4). Previous work shows many of these areas to have weak to moderate, yet often significant, NAOI-P correlations; such as for western and northern England (West et al, 2019), northern Germany (Riaz et al, 2017), southern France (Massei et al, 2007). Indeed, many studies in these regions have found skilful prediction of winter rainfall (and other water resource variables) through use of the historical NAOI-P relationship, despite the non-stationary reported here (Ionita & Nagavciuc, 2020; Moreira et al, 2016; Rasouli et al, 2020; Rousi F I G U R E 3 Ten year moving correlation analysis for selected Western Europe nation-based regions.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, it also implies that the WNAO is unable to fully explain the variability of UK winters because the complexity of weather types and associated temperature and rainfall patterns through the season cannot be fully accounted for by this single index. The influence of WNAO may also differ regionally across the UK, for example for rainfall across the north‐west compared to the south‐east, which overall UK rainfall statistics will tend to smooth out (West et al, ).…”
Section: Synoptic Situationmentioning
confidence: 99%